PENGEMBANGAN ENKAPSULAT NANOEMULSI EKSTRAK KULIT MANGGIS (Garcinia mangostana L.): UJI DISOLUSI IN VITRO DAN AKTIVITAS PENGHAMBATAN ENZIM Α-AMILASE: Development of Nanoemulsion Encapsulated Mangosteen Peel Extract (Garcinia mangostana L.): In Vitro Dissolution and α-Amylase Inhibition Activity - Rizki, Tri; Yasni, Sedarnawati; Yuliani, Sri; Muhandri, Tjahja (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2024)
This study aims to develop a nanoemulsion encapsulation system for mangosteen peel extract to enhance the stability and bioavailability of its bioactive compounds, primarily xanthones. The research focused on optimizing the ethanol concentration for extraction, the surfactant type for nanoemulsion synthesis, and the encapsulant materials. Encapsulation efficiency, dissolution characteristics, and α-amylase inhibition activity were evaluated to assess its potential for diabetes management. Encapsulation using maltodextrin and gum arab achieved the highest efficiency (97.93%) and antioxidant capacity (572.92 µg AEAC/g). In vitro dissolution tests showed enhanced phenolic release rates in both acidic (94.57%) and alkaline (94.51%) media compared to non-encapsulated extracts. However, the encapsulated extract exhibited slightly lower α-amylase inhibition (74.10%) than the crude extract (78.61%) due to slower bioactive release. These findings suggest that nanoemulsion encapsulation with maltodextrin and gum arab improves the delivery and functionality of mangosteen peel extract, presenting promising applications in functional food development for diabetes management.